Tubercular liver abscess rupturing into the pleural cavity: a rare complication. (October 2019) - Bansal, Mohit; Dalal, Poonam; Kadian, Yogender; Malik, Navneeti
Liver abscesses, either pyogenic or amoebic, with or without the involvement of the pleura, are not infrequently encountered in children. Isolated tubercular liver abscess without active pulmonary, gastrointestinal or other clinical evidence of tuberculosis is, however, rare and more so its rupture into the pleura. We report a case of a 14-year-old girl who presented with a liver abscess rupturing into the pleura causing an empyema. Successful management was achieved by intercostal tube drainage and antitubercular treatment.